The Challenges of Islamic Organizations in Promoting Moderation in Indonesia - Hasse Jubba; Jaffary Awang; Siti Aisyah Sungkilang (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2021)
Two leading Islamic organisations in Indonesia, Muhammadiyah and Nahdlatul Ulama (NU) have moderation in their missionary vision to create a tolerant, open, and civilised society. This paper explores the challenges of realising Islamic moderation in Indonesia, especially those driven by Muhammadiyah and NU. The data used as the basis for the analysis were obtained from interviews and document studies. The challenge of Islamic moderation initiated by these two organisations is the rise of conservative groups, which have received vast space from the data obtained. This paper emphasised that the rise of conservative groups has resulted in weak respect for other groups. There is even a tendency to resist Islamic groups outside their group. This paper is limited to the internal challenges to Islamic moderation in Indonesia carried out by Muhammadiyah and NU, particularly related to the rise of conservative Islamic groups. Therefore, this paper suggests conducting various studies to provide a basic framework for jointly building a commitment to implement Islamic moderation in Indonesia by looking at other civil society organisations.